Precision of verbal feedback affects accuracy of motor skill performance - Zalech, M.; Bujak, Z. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The study sought to determine whether the precision of verbal feedback on knowledge of results affected the accuracy of motor skill performance with various parameters.